Analysis of the Relationship Between Carrageenan Content of Seaweed (Kappaphycus alvarezii Doty, 1986) with Water Quality in The Makassar Strait - Sudar, Kasmawati; Latief, Nursidi; Cahyono, Indra; Kantun, Wayan (Agrikan Jurnal Agribisnis Perikanan, 2024)
Analysis of the relationship between carrageenan content of seaweed (Kappaphycus alvarezii Doty, 1986) with water quality in the Makassar Strait) Kappaphycus alvarezii seaweed is experiencing high demand and supply as an industrial raw material, so it is important to analyze its carrageenan content. This study aims to analyze the carrageenan content of Kappaphycus alvarezii seaweed cultivated in estuaries, around corals and the open sea. This research is classified as a type of quantitative research with observation methods. The research was conducted from September to October 2022 in the waters of the Makassar Strait. The results showed that the carrageenan content of red seaweed Kappaphycus alvarezii as a whole ranged from 53.05 to 58.37% (55.84 ± 1.57%) with details of 55.52 ± 0.242% for carrageenan content in samples from the estuary, 55.57 ± 2.671% for the area around the reef and 56.43 ± 1.388% for the open sea. The highest carrageenan content of Kappaphycus alvarezii seaweed was obtained in the high seas cultivation areas.